2015
DOI: 10.11648/j.jfns.20150304.13
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Fresh Vegetables and Fruits Collected from Supermarkets in Istanbul, Turkey

Abstract: Abstract:Two hundred sixty one samples, collected from supermarkets in Istanbul, Turkey. All samples were analysed for aerobic mesophilic bacterial counts (AMC), aerobic psychrotrophic bacterial counts (APC), enumeration of yeasts and moulds (YM), coliforms, Escherichia coli and detection of Escherichia coli O157:H7, Salmonella spp., Listeria monocytogenes, thermotolerant Campylobacter spp. AMC ranged from 2.95 to 3.75 log 10 CFU/g. APC ranged from 0 to 3.55 log 10 CFU/g. The highest counts of coliforms were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 40 publications
(57 reference statements)
5
22
5
Order By: Relevance
“…The coliform counts on spinach in this study were similar to the results obtained for baby spinach (2.0 log CFU/g to 5 log CFU/g) from a farm and processing facility supplying retailers in the formal sector in South Africa (25). In contrast the coliform counts for spinach obtained from supermarkets in Istanbul, Turkey ranged between 2.95 log CFU/g to 3.45 log CFU/g which was approximately 1.5 log CFU/g to 2.5 log CFU/g lower that the maximum coliform counts measured for spinach from formal and informal suppliers in this study (7). In a recent study by Xu et al (47) a total coliform mean value of 6 log CFU/g was measured for leafy green vegetables (lettuce, spinach, Swiss chard and salad greens) which is comparable to the to the spinach mean values of 4.6446 log CFU/g (retailer samples) and 4.9734 log CFU/g (street vendor samples) measured in the current investigation.…”
Section: Phylogenetic Group Distributioncontrasting
confidence: 70%
“…The coliform counts on spinach in this study were similar to the results obtained for baby spinach (2.0 log CFU/g to 5 log CFU/g) from a farm and processing facility supplying retailers in the formal sector in South Africa (25). In contrast the coliform counts for spinach obtained from supermarkets in Istanbul, Turkey ranged between 2.95 log CFU/g to 3.45 log CFU/g which was approximately 1.5 log CFU/g to 2.5 log CFU/g lower that the maximum coliform counts measured for spinach from formal and informal suppliers in this study (7). In a recent study by Xu et al (47) a total coliform mean value of 6 log CFU/g was measured for leafy green vegetables (lettuce, spinach, Swiss chard and salad greens) which is comparable to the to the spinach mean values of 4.6446 log CFU/g (retailer samples) and 4.9734 log CFU/g (street vendor samples) measured in the current investigation.…”
Section: Phylogenetic Group Distributioncontrasting
confidence: 70%
“…On the other hand, Weldezgina and Muleto in Ethiopia [19] and Nyenje et al [20] in South Africa observed narrower ranges of high AMC from 6.94 to 8.06 and from 6.3 to 6.8 log CFU/g, respectively). A much lower AMC range of 2.95-3.75 log CFU/g was reported by Buyukunal et al [21] in Turkey. The difference in the ACC mean values may be attributed to the different areas of vegetables cultivation and different irrigation sources.…”
Section: Discussionmentioning
confidence: 55%
“…This was in agreement with Khalil and Gomaa [18] who found that lettuce had the lowest mean AMC (3.15±0.46 log CFU/g). On the contrary, Buyukunal et al [21] in Turkey reported that green leaf lettuce, iceberg lettuce, cos lettuce, and spinach had significantly higher microbial loads than other tested commodities. Moreover, Halablab et al [23] in Lebanon documented that all lettuce samples collected from different locations in Bekaa Valley had higher incidence of aerobic organisms than any other vegetable samples collected from the same locations.…”
Section: Discussionmentioning
confidence: 89%
“…Yeast and Rhodotorula species predominated other fungi followed by Aspergillus rooms which are generally consumed raw or cooked with a main dish, in a mixed dish, as an appetizer or in a salad [1]. Unprocessed (raw) fruits and vegetables are known to contain certain essential components such as carbohydrates, proteins, vitamins and minerals which are of vital importance to the health of humans [2]. In most countries, people consume raw vegetables and fruits because of the health benefits such as their ability to prevent diseases such as cancer, diabetes, cardiovascular diseases and stroke [3].…”
Section: Introductionmentioning
confidence: 99%